Children «on the side»: feeding industry on territory of Tavrida Province in late XIX–early XX centuries - V. A. Maslennikova (Омский научный вестник: Серия "Общество. История. Современность")
Russian Empire in the second half of the XIX–early XX centuries gradually entered the era of modernization of political, economic and social institutions. The disintegration of the patriarchal family entailed a massive exodus of women to cities, which in turn turned out to be on the quantitative indicators of illegitimate births. Lack of funds for food, prompted mothers to leave the child to the mercy of fate. Statistical data is stating that the foundlings grew from year to year. By the end of the XIX century each issue of the periodical press, published in the territory of the Tauride province, contained several reports about foundlings. All children were sent to an orphanage. A wet nurse was assigned to the child, who was supposed to replace his mother. The direction of the research is to describe the patronage system in the Tauride province of the late XIX–early XX centuries